EVALUASI KEBERHASILAN KOPERASI SERBA USAHA PETERNAK MOTIVASI DO’A IKHTIAR TAWAKKAL (KSUP MDIT) KABUPATEN TANGGAMUS, LAMPUNG BERDASARKAN PENDEKATAN TRIPARTITE - Tri Uli Jalika; Dyah Aring Hepiana Lestari; Ani Suryani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
This research aims to analyze:  cooperative’s performance as business entities,  cooperative’s contribution towards development, the economic advantage of cooperative for members, the non economic advantages (satisfaction) of cooperative members.  This research uses a case study method and the research location at “Serba Usaha Peternak Motivasi Do’a Ikhtiar Tawakkal” Cooperative (KSUP MDIT) in Tanggamus District, Lampung.  Total respondents were 55 members of the cooperative taken by using simple random sampling and consisted of members with the ownership of 0-5 goats, 6-10goats, and 11-15 goats.  Data were analyzed by using descriptive analysis and Importance Performance Analysis method.  The results showed that: business entities performance of KSUP MDIT included into quality category.  The KSUP MDIT hasn’t given maximal contribution towards the development. The more cattle that members of the cooperative have, the more the economic advantages they get. Non economic advantages (satisfactions) of members with service performance and fulfilment of member’s needs were in high category.Key words: advantage, cooperative, goat’s cattle, satisfaction